If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 5x = -40 Solving 9 + 5x = -40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5x = -40 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = -40 + -9 5x = -40 + -9 Combine like terms: -40 + -9 = -49 5x = -49 Divide each side by '5'. x = -9.8 Simplifying x = -9.8
| 1-12x+2x=3x+2 | | 2r-4+3r=25 | | 4(a+7)-2a=a-3 | | 22x-8(2x-3)=50 | | 30+x=31 | | 5y-5=7+4(y-4) | | 8-5(a+2)=-6a+9 | | 15y+3+7x=180 | | 3x-18=-6x | | 4x-23=12x+53 | | 4x^2+72+324=0 | | 5p-(3p+p)=6p+1 | | 12x-2(4x+-4)=-24 | | ?8c+21=2c+1 | | 3x-4=8x+10 | | x+6(4)=18 | | 6x-2x-6=5 | | G^2-20g+10=0 | | -75-k=-92 | | 15x^4-30x^2+15x=0 | | -27+15x=33-15 | | x+(3x-22)=180 | | A=4tg(2x+1)+3tg(3x-1) | | 11x+49=0 | | ln(3)=8 | | 2+3(t+4)=11 | | 5y-28=6x | | 4x+5=-8x-7 | | .04x+8=24 | | 2(18-6y)-3y=-24 | | 9=3(k-1)+k | | y=cos(2y) |